PENINGKATAN KEMAMPUAN PENALARAN MATEMATIKA DENGAN PENDEKATAN SCIENTIFIC TERINTEGRASI PADA MODEL PROBLEM SOLVING - Ika Septi Hidayati (Intersections, 2020)
The purpose of this study was to determine the application of an integrated scientific approach to the correct problem solving model in order to improve the reasoning abilities of the fifth grade students of SD Negeri Prembulan. The results of this study indicate that: (1) In general, the application of the integrated scientific approach to the correct problem solving model is effective in improving mathematical reasoning skills, (2) Increasing mathematics reasoning of the fifth grade students of SD Prembulan in the pre-cycle by 50.05% in the cycle I amounted to 76.31% in the second cycle of 85.39%